A lightweight security scheme for advanced metering infrastructures in smart grid - S. M. Salim Reza; Afida Ayob; Md Murshedul Arifeen; Nowshad Amin; Mohd Hanif Md Saad; Aini Hussain (Bulletin of Electrical Engineering and Informatics, 2020)
Smart Grid (SG) enlarges the traditional power grid into a new dimension where millions of electronic devices relate to each other through Advanced Metering Infrastructures (AMI) network using information and communication technology (ICT). The integration of ICT to the traditional power grid opens the path for the adversaries to invade through various cyber-attacks. Resource constrained electronic devices connected in AMI with the SG claims for faster, low power, less processing time and overall lightweight security schemes to prevent the cyber-attacks and to make the grid secure from adversaries. In this paper, a lightweight security scheme has been proposed consolidating ChaCha20 data encryption method, chaos based key generation and public key-based authentication scheme. Mathematical analysis shows that the proposed scheme is suitable to be used in SGs in terms of low power, less processing time and high throughput which makes it lightweight and faster. This scheme also prevents any kind of timing attacks such as replay attack.